Heat Stress Is More Damaging to Superior Spikelets than Inferiors of Rice (Oryza sativa L.) due to Their Different Organ Temperatures - Fu, Guanfu; Feng, Baohua; Zhang, Caixia; Yang, Yongjie; Yang, Xueqin; Chen, Tingting; Zhao, Xia; Zhang, Xiufu; Jin, Qianyu; Tao, Longxing (Frontiers in Plant Science, 2016)
In general, the fertility and kernel weight of inferior spikelets of rice (Oryza Sativa L.) are obviously lower than those of superior spikelets, especially under abiotic stress. However, heat stress at anthesis seems to cause more damage to superior spikelets than to inferior spikelets. When rice plants were subjected to heat stress of 40℃ at anthesis, a greater decrease in fertility and kernel weight was observed in superior spikelets compared to inferior spikelets. This decrese has primarily been described to their different organ temperatures, in which the temperature of the superior spikelets was significantly higher than that of inferior spikelets. We inferred the differences in canopy temperature, light intensity and panicle types, were the primary reasons for the temperature difference between superior and inferior spikelets. Under heat stress, the fertility and kernel weight of superior and inferior spikelets decreased as the panicle numbers per plant were reduced, which was accompanied by the significantly increased canopy temperatures. Thus, it was suggested that the rice plant with characteristic features of an upright growth habit and loose panicles might be more susceptible to heat stress resulting from their higher canopy and spikelets temperatures.